2021
DOI: 10.1021/acs.jchemed.0c01231
|View full text |Cite
|
Sign up to set email alerts
|

Introducing ATR-FTIR Spectroscopy through Analysis of Acetaminophen Drugs: Practical Lessons for Interdisciplinary and Progressive Learning for Undergraduate Students

Abstract: Infrared (IR) spectroscopy is a vibrational spectroscopic technique useful in chemical, pharmaceutical, and forensic sciences. It is essential to identify chemicals for reasons spanning from scientific research and academic practices to quality control in companies. However, in some university degrees, graduate students do not get the proficiency to optimize the experimental parameters to obtain the best IR spectra; to correlate the IR spectral bands with the molecular vibrations (chemical elucidation); to hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…In the case of the f-MWCNT/N-(2-C 2 H 5 O) ED­(CH 3 COONa) 3 composite, relatively less intense −OH and −C–H peaks were observed, which might be due to the effect of composite formation. In addition, the f-MWCNT/N-(2-C 2 H 5 O) ED­(CH 3 COONa) 3 composite resulted in peaks at 1592, 1416, 1333, 1261, 1125, and 1081 cm –1 associated with −CO/–CC, −C–H/–OH bending, sulfate group, −C–O, −CN/–C–C, and −C–N groups, respectively (Figure B­(c)). , For the f-MWCNT/DETA (CH 3 COOH) 5 composite, comparatively highly intense −OH and −C–H peaks were observed. In addition, the f-MWCNT/DETA (CH 3 COOH) 5 composite showed peaks at 1583, 1405, 1332, 1262, and 1115 cm –1 for −CO/–CC, −C–H/–OH bending, sulfate group, −C–O, and −CN/–C–C, respectively (Figure B­(d)). , From the above-mentioned observations, it has been confirmed that the effective formations of f-MWCNT, f-MWCNT/N-(2-C 2 H 5 O) ED­(CH 3 COONa) 3 , and f-MWCNT/DETA (CH 3 COOH) 5 have occurred.…”
Section: Resultsmentioning
confidence: 97%
“…In the case of the f-MWCNT/N-(2-C 2 H 5 O) ED­(CH 3 COONa) 3 composite, relatively less intense −OH and −C–H peaks were observed, which might be due to the effect of composite formation. In addition, the f-MWCNT/N-(2-C 2 H 5 O) ED­(CH 3 COONa) 3 composite resulted in peaks at 1592, 1416, 1333, 1261, 1125, and 1081 cm –1 associated with −CO/–CC, −C–H/–OH bending, sulfate group, −C–O, −CN/–C–C, and −C–N groups, respectively (Figure B­(c)). , For the f-MWCNT/DETA (CH 3 COOH) 5 composite, comparatively highly intense −OH and −C–H peaks were observed. In addition, the f-MWCNT/DETA (CH 3 COOH) 5 composite showed peaks at 1583, 1405, 1332, 1262, and 1115 cm –1 for −CO/–CC, −C–H/–OH bending, sulfate group, −C–O, and −CN/–C–C, respectively (Figure B­(d)). , From the above-mentioned observations, it has been confirmed that the effective formations of f-MWCNT, f-MWCNT/N-(2-C 2 H 5 O) ED­(CH 3 COONa) 3 , and f-MWCNT/DETA (CH 3 COOH) 5 have occurred.…”
Section: Resultsmentioning
confidence: 97%
“…The signal at 1753 cm −1 was assigned to the valence vibration C=O of the carbonyl group (ν C=O ) of the five membered alpha lactone ring system. The intense band at 1650 cm −1 arises from C=C stretching vibrations (ν C=C ring stretching) [48,49]. Others vibrational bands are observed in the region 1500-1000 cm −1 , which are connected with the C-H deformation modes (CH 2 scissoring and wagging, and bending of the CH group), C-O-C stretching and C-O-H bending [48,50].…”
Section: Characterization Of Raw and Composite Materialsmentioning
confidence: 99%
“…Similar to FTIR, although there are existing laboratory exercises implementing the use of chemometrics, a highly interdisciplinary field, which employs applied mathematics, computer science, and multivariate statistics using methods employed in core-data analytic problems, the majority of these are primarily targeted toward classification purposes (i.e., principal component analysis, factor analysis). , Further, although the chemical education community acknowledges the need for student training in various computational methods, there are limited pedagogical materials and no simplified or standardized way of incorporating these into the curriculum, especially in the use of instrumentation for data generation and consequent chemometric quantitative analysis of the same data. There are some studies, however, that are dedicated to the use of instrumentation and chemometrics for quantitative determination of analytes but are typically introduced in advanced analytical courses. , Further, many of these studies cannot also be directly implemented in the undergraduate curriculum because of the limitation of having to purchase expensive and not so user-friendly chemometric software packages.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the concept of Fourier transform infrared (FTIR) spectroscopy has been known for more than a century, it took more than 60 years for its application to be widely recognized as a potential analytical tool . Today, due to rapid commercial development and extensive research, it is considered to be one of the most powerful chemical techniques, and has had a wide array of successes in agriculture, biomaterials, chemistry, and environmental science among others. A wide variety of experiments have been introduced to students allowing them to learn more about FTIR spectroscopy, specifically on the use of an attenuated total reflectance (ATR) accessory for acquiring the infrared spectra of unknown solid and liquid organics, of inorganic solids synthesized by students, studying the adsorption of ions from solution onto oxide particle surfaces, and structural analysis of nanofilms. Further, a variety of approaches have also been introduced to students to enhance their knowledge on spectral interpretation and understanding the FTIR such as by using a spreadsheet exercise, computing the infrared spectrum using the interferogram data, and by visual spectra comparison and statistical analysis and matching. …”
Section: Introductionmentioning
confidence: 99%